Efficient hyperactive piggyBac transgenesis in Plodia pantry moths - Heryanto, Christa; Mazo-Vargas, Anyi; Martin, Arnaud (Frontiers in Genome Editing, 2022)
While piggyBac transposon-based transgenesis is widely used in various emerging model organisms, its relatively low transposition rate in butterflies and moths has hindered its use for routine genetic transformation in Lepidoptera. Here, we tested the suitability of a codon-optimized hyperactive piggyBac transposase (hyPBase) in mRNA form to deliver and integrate transgenic cassettes into the genome of the pantry moth Plodia interpunctella. Co-injection of hyPBase mRNA with donor plasmids successfully integrated 1.5-4.4 kb expression cassettes driving the fluorescent markers EGFP, DsRed, or EYFP in eyes and glia with the 3xP3 promoter. Somatic integration and expression of the transgene in the G0 injected generation was detectable from 72-hr embryos and onward in larvae, pupae and adults carrying a recessive white-eyed mutation. Overall, 2.5% of injected eggs survived into transgene-bearing adults with mosaic fluorescence. Subsequent outcrossing of fluorescent G0 founders transmitted single-insertion copies of 3xP3::EGFP and 3xP3::EYFP and generated stable isogenic lines. Random in-crossing of a small cohort of G0 founders expressing 3xP3::DsRed yielded a stable transgenic line segregating for more than one transgene insertion site. We discuss how hyPBase can be used to generate stable transgenic resources in Plodia and other moths.